Operative techniques and morbidity with subthalamic nucleus deep brain stimulation in 100 consecutive patients with advanced Parkinson's disease. Issue 1 (16th December 2005) - Goodman, R R; Kim, B; McClelland, S; Senatus, P B; Winfield, L M; Pullman, S L; Yu, Q; Ford, B; McKhann, G M
Abstract : Objective: Subthalamic nucleus (STN) stimulation for patients with medically refractory Parkinson disease (PD) is expanding. Reported experience has provided some indication of techniques, efficacy, and morbidity, but few centres have reported more than 50 patients. To expand this knowledge, we reviewed our experience with a large series of consecutive patients. Methods: From March 1999 to September 2003, 191 subthalamic stimulator devices (19 unilateral) were implanted in 100 patients with PD at New York Presbyterian Hospital/Columbia University Medical Center. Sixteen patients had undergone a prior surgery for PD (pallidotomy, thalamotomy, or fetal transplant). Microelectrode guided implantations were performed using techniques similar to those described previously. Electrode implantation occurred 1–2 weeks before outpatient pulse generator implantation. Results: Reductions of dyskinesias and off severity/duration were similar to prior published reports. Morbidity included: 7 device infections (3.7%), 1 cerebral infarct, 1 intracerebral haematoma, 1 subdural haematoma, 1 air embolism, 2 wound haematomas requiring drainage (1.0%), 2 skin erosions over implanted hardware (1.0%), 3 periprocedural seizures (1.6%), 6 brain electrode revisions (3.1%), postoperative confusion in 13 patients (6.8%), and 16 battery failures (8.4%). Of the 100 patients, there were no surgical deaths or permanent new neurological deficits. The average hospital stay for all 100 patients was 3.1 days. Conclusion: Subthalamic stimulator implantation in a large consecutive series of patients with PD produced significant clinical improvement without mortality or major neurological morbidity. Morbidity primarily involved device infections and hardware/wound revisions.